Reimagining Perinatal Palliative Care: A Broader Role for Support in the Face of Uncertainty. Issue 4 (October 2022) - Lord, Sarah; Williams, Rebecca; Pollard, Lindsay; Ives-Baine, Lori; Wilson, Carolyn; Goodman, Kira; Rapoport, Adam
Perinatal medicine is confronted by a growing number of complex fetal conditions that can be diagnosed prenatally. The evolution of potentially life-prolonging interventions for the baby before and after birth contributes to prognostic uncertainty. For clinicians who counsel families in these circumstances, determining which ones might benefit from early palliative care referral can be challenging. We assert that all women carrying a fetus diagnosed with a life-threatening condition for which comfort-focused care at birth is one ethically reasonable option ought to be offered palliative care support prenatally, regardless of the chosen plan of care. Early palliative care support can contribute to informed decision making, enhance psychological and grief support, and provide opportunities for care planning that includes ways to respect and honor the life of the fetus or baby, however long it may be.